Adam Wiegner in the Light of Leonard Nelson’s Problem of Knowledge - Kubalica, Tomasz (Folia Philosophica, 2017)
The subject of the article is the influence of the broadly understood NeoKantianism on the assimilating of Kantians ideas of critical philosophy (critical method) in Poland. I would like to present a philosophical and historical reflection on the dissertation of professor of University of Poznan Adam Wiegner (1889—1967), entitled Zagadnienie poznawcze w oświetleniu L. Nelsona (Problem of Knowledge in the Light of L. Nelson, 1925), in which he undertook a critical analysis of Nelson’s problem of impossibility of the theory of knowledge and possibilities of the metaphysics. The main aim of the article is to present the Neo-Kantians (as well as the Neo-Friesians) context of the above-mentioned Wiegners dissertation and to reflect on the reception of Nelson’s thoughts in Poznań. I would like to show that, contrary to the schematic simplification, Neo-Kantian thought had a significant influence on the shape of philosophy in Poland.